2020
DOI: 10.3390/ma13153277
|View full text |Cite
|
Sign up to set email alerts
|

Crosslinking Dynamics and Gelation Characteristics of Photo- and Thermally Polymerized Poly(Ethylene Glycol) Hydrogels

Abstract: The crosslinking behaviors and gelation features of poly(ethylene glycol) (PEG) hydrogels were scrutinized during the UV and thermal polymerizations of mixtures of poly(ethylene glycol) methacrylate (PEGMA, monomer) and poly(ethylene glycol) dimethacrylates (PEGDMAs, crosslinkers). The real-time crosslinking behavior of the PEG hydrogels was quantified as a function of the UV irradiation time and reaction temperature during the UV and thermal polymerization, respectively, using real-time FT-IR spectrometry and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 29 publications
3
6
0
Order By: Relevance
“…Figure 1 shows the UV-Vis spectra before and after crosslinking for the novel PIs. In general, for all new PEG-DA hydrogels, we find spectra shifted somewhat toward higher wavelengths compared to the pure PIs [ 24 , 25 ], while crosslinking tends to cause a small shift toward lower wavelengths, as already substantiated in the literature [ 26 ].…”
Section: Resultssupporting
confidence: 78%
“…Figure 1 shows the UV-Vis spectra before and after crosslinking for the novel PIs. In general, for all new PEG-DA hydrogels, we find spectra shifted somewhat toward higher wavelengths compared to the pure PIs [ 24 , 25 ], while crosslinking tends to cause a small shift toward lower wavelengths, as already substantiated in the literature [ 26 ].…”
Section: Resultssupporting
confidence: 78%
“…Figure 6 shows the UV-Vis spectra before and after crosslinking for the novel PIs. In general, for all new PEG-DA hydrogels, we find the absorption band of the dye in the polymer matrix shifted somewhat toward higher wavelengths compared to the pure PIs [44,45], while crosslinking tends to cause a small shift toward lower wavelengths again, as already substantiated in the literature [46].…”
Section: Uv: Vis Spectrasupporting
confidence: 85%
“…For the other treated electrolytes, this peak is almost non existent and a polymerization with a high rate of conversion is deduced. Note that the C=O peak in the methacrylate group was slightly shifted toward a higher wavenumber, from 1716 to 1725 cm −1 , implying an increased carbonyl bond strength due to the loss of conjugation between the olefin and carbonyl groups during UV curing, as is already substantiated in the literature [37,38]. Considering the C=C peak deacrease and the C=O peak shift of the treated electrolytes, it can be concluded that the addition of pigments doesn't influence the polymerization conversion.…”
Section: Electrolyte Characterizationsupporting
confidence: 65%